Innovation of control technology for smart fuzes: precise detonation and efficient damage via a ternary cascade controller - Liu, Peng; Li, Jian; Yu, Hang; Zhang, He (Frontiers in Physics, 2024)
The traditional theory on dynamic open-loop control of fuzes has been unable to satisfy the demand for smart fuze control. After analyzing the time-space recognition and process control as the basis of fuze detonation control, three key issues of smart fuze control are summarized herein. Furthermore, three types of controllers are constructed: detection, state, and detonation controllers, which complete the precise detonation control of ammunition under the interference of complex multi-physics environments and achieve efficient damage to the target. Based on the above-mentioned controllers, the design theory of the ternary cascade control of the smart fuze is established. In addition, the technical system of the ternary cascade control theory is reviewed, and the latest progress in control strategy design, environment modeling, target modeling, and other fields is summarized in detail. Finally, the development demand and technology trend of intelligent fuze control technology for future intelligent warfare are prospected.